Law Enforcement Efforts Against Criminal Offences Of Fraud Based On Online / Electronic Transactions - Satria Muhammad; Syiful Asmi Hasibuan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Fraudulent acts are currently flourishing following the era and technology advancement. Laws and regulations are made to anticipate this, but the existing laws and regulations seem like unable to combat the crime amid their increase in occurrences. This research aims to: firstly, to identify law enforcement against the e-commerce-based frauds; and secondly, to identify the obstacles in criminal law enforcement against e-commerce- based frauds. This research was conducted by using normative juridical method through literature research by examining secondary data including legislation, research results, scientific journals and references. The research results describe that the e-commerce- based fraudulent acts in principle are similar to the conventional frauds but differ in the evidences or means of action as the latter uses electronic systems (computers, internet, telecommunications equipment). Therefore, the legal enforcement against this kind of frauds is still under the applicability of the Indonesian Criminal Code and the Law No. 19 of 2016 regarding Amendments to the Law No. 11 of 2008 regarding Information and Electronic Transactions. Further, the law enforcement against the fraudulent acts in electronic-based transactions has been prevented at least by the following five factors, the laws and regulations, law enforcers, infra-structure or facilities that support the law enforcement, community and cultural factors.